The effect of advertising and brand image on consumer purchase decisions at CV. Berkah Gerrytex Bandung - Ine Aprianti; Siti Ainun Nining Safitri; Lucy Nurfadilah; Agrie Wahyudi Khrismawan; Rika Kartika (Sean Institute, 2024)
CV. Berkah Gerrytex Bandung is a company that markets textile products. Textile is a material made from fiber that is processed in the form of cloth or yarn as a material for making clothing and other products. The problem in this research is Brand Image and Advertising on CV. Berkah Gerrytex is considered not good so that the public or consumers do not know much about the company's brand so that they are less interested in buying it. This study aims to determine whether there is influence of advertising variables and brand image variables on consumer purchasing decisions. The research method used in this research is descriptive and verification. The population in this study are consumers of CV. Berkah Gerrytex as many as 56 consumers collected. Testing and analysis of this research includes the classical assumption test, hypothesis testing, the coefficient of determination and multiple linear regression analysis. The programs and applications used to perform data analysis and data processing are using the IBM Statistical Package For Social Sciences (SPSS) version 26.00. Based on the results of the research conducted, it shows that advertising and brand image have a simultaneous effect on consumer purchasing decisions. The results of the study partially show that advertising has a positive effect on purchasing decisions at CV. Berkah Gerrytex. Meanwhile, brand image has a partial effect on purchasing decisions at CV. Blessings Gerrytex. From the results of this study it can be concluded that there is an influence of advertising and brand image on consumer purchasing decisions at CV. Berkah Gerrytex is 60,3% while the rest is influenced by other variables such as price, service quality and others.